A Mamdani Fuzzy Model to Choose Eligible Student Entry - Agus Nursikuwagus; Agis Baswara (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper presented about study that have been created a new student choosing system by using fuzzy mamdani inference systems method. Fuzzy mamdani is used because it has characteristics such as human perceptions on choosing of students with some specified criteria. The choosing studens who want entry to the school have been difficult if it is manually process. With the fuzzy mamdani, the process can be possible completed execute and can be reduced the time of choose. To accomplish the process, the fuzzy variable is created by the national final exam scores, report grade, general competency test, physical test, interview and psychological test. Based on testing 270 data, the fuzzy mamdani has been reached 75.63% accuracy.